Dopamine D1 receptor-mediated β-arrestin signaling: Insight from pharmacology, biology, behavior, and neurophysiology. (July 2022) - Yang, Yang; Lewis, Mechelle M.; Huang, Xuemei; Dokholyan, Nikolay V.; Mailman, Richard B.
Abstract: The awareness of the potential importance of functional selectivity/biased signaling has led to the discovery of biased compounds as both research tools and novel drugs. A major pan-receptor focus has been to identify GPCR-selective ligands that have bias in G protein-dependent vs. β-arrestin related signaling. Although this field has exploded during the past two decades, it is only recently that highly β-arrestin biased ligands for the dopamine D1 receptor were reported. We now summarize important pharmacological, molecular, and cellular studies relevant to D1 -mediated β-arrestin-related signaling. It is intriguing that many results emerged from behavioral and physiological studies implying that bias toward or against D1 -mediated β-arrestin either can improve or impair functional outcomes. We discuss the importance of understanding the translatability of cell and animal models to have more precise functional targeting to harness the value of this signaling pathway.